Alfabetização científica no ensino médio por meio do ensino por investigação - Bosco, Elis Marina Ribeiro (2018)
This study evaluated whether a sequence of research teaching promotes scientific literacy in high school students. For that, a didactic sequence was developed and applied through a semester discipline, of which the researcher was fully in charge of teaching. It had as its generating theme the interdisciplinary concept of "Energy and Environment" problematized in the relations between science, technology and society, through the strategy of "Teaching by Research" and theoretical presuppositions of the field of "Scientific Literacy". The sequence was applied with students of the 2nd and 3rd years of the Secondary Education of the Teaching and Research Center Applied to Education of the UFG. This is a qualitative research that had as data source field notes, audio and video recordings, and final papers of the students, having content analysis as technique and Scientific Literacy as a theoretical reference in the interpretation of data. Through the results and analysis of each group, considering the three structuring axes and the indicators of the Scientific Literacy, it was possible to identify the use of terms, knowledge and fundamental scientific concepts about their themes: understanding the nature of science and ethical and the understanding of the relationships between science, technology, society and the environment, the collection and testing of hypotheses, justification, prediction and explanation of the research carried out by each of the groups. I conclude that a Sequence of Teaching by Research promotes Scientific Literacy in high school students.